New World genera of Galerucinae Latreille, 1802 (tribes Galerucini Latreille, 1802, Metacyclini Chapuis, 1875, and Luperini Gistel, 1848): an annotated list and identification key (Coleoptera: Chrysomelidae) - Viswajyothi, Keezhpattillam; Clark, Shwan M. (European Journal of Taxonomy, 2022)
An annotated list, including information on type species, distribution, and number of species, is provided for all of the non-flea-beetle galerucine genera known to occur in the New World (tribes Galerucini, Metacyclini, and Luperini). A diagnostic key to the genera is provided. Habitus illustrations are provided for most genera. The following new genera are proposed: Amplioluperus gen. nov., Cornuventer gen. nov., Geethaluperus gen. nov., Megarhabda gen. nov., Mexiluperus gen. nov., Monoaster gen. nov., Pyesexora gen. nov., Texiluperus gen. nov., Trachyelytron gen. nov. and Yingabruxia gen. nov. The following new taxonomic placements are proposed: Microbrotica Jacoby, 1887 is transferred from the tribe Metacyclini to the section Diabroticites Chapuis, 1875 (tribe Luperini, subtribe Diabroticina Chapuis, 1875); Pteleon Jacoby, 1888 is transferred from the section Exosomites Wilcox, 1973 (tribe Luperini, subtribe Luperina Gistel, 1848) to the section Scelidites Chapuis, 1875 (subtribe Luperina). The following new combinations are proposed: Luperodes histrio Horn, 1895, Luperus maculicollis LeConte, 1884, and Scelolyperus cyanellus Horn, 1895 are transferred from Pseudoluperus Beller & Hatch, 1932 to Amplioluperus; Luperodes tuberculatus Blake, 1942 is transferred from Pseudoluperus to Cornuventer; Luperus flavofemoratus Jacoby, 1888 is transferred from Pseudoluperus to Geethaluperus; Trirhabda obscurovittata Jacoby, 1886 is transferred from Trirhabda LeConte, 1865 to Megarhabda; Cneorane nigripes Allard, 1889 is transferred from Scelida Chapuis, 1875 to Metacycla Baly, 1861; Luperodes wickhami Horn, 1893 and Luperus dissimilis Jacoby, 1888 are transferred from Pseudoluperus to Mexiluperus; Scelolyperus tenuimarginatus Bowditch, 1925, is transferred from Scelida to Mimastra Baly, 1865 and is synonymized with Mimastra semimarginata Jacoby, 1886 syn. nov.; Pseudoluperus fulgidus Wilcox, 1965 and Pseudoluperus linus Wilcox, 1965 are transferred from Pseudoluperus to Monoaster; Crioceris detrita detrita Fabricius, 1801, Malacosoma detrita laevicollis Jacoby, 1887, Pyesia detrita meridionalis Bechyné, 1958, Pyesia elytropleuralis elytropleuralis Bechyné, 1958, and Pyesia elytropleuralis subalutacea Bechyné, 1958 are transferred from Pyesia Clark, 1865 to Pyesexora; Luperodes spretus Horn, 1893 and Luperodes texanus Horn, 1893 are transferred from Pseudoluperus to Texiluperus; Chthoneis smaragdipennis Jacoby, 1888 is transferred from Platymorpha Jacoby, 1888 to Trachyelytron; Luperus albomarginatus Jacoby, 1888 is transferred from Pseudoluperus to Trichobrotica Bechyné, 1956; and Galleruca sordida LeConte, 1858, Monoxia apicalis Blake, 1939, Monoxia batisia Blatchley, 1917, and Monoxia brisleyi Blake, 1939 are transferred from Monoxia LeConte, 1865 to Yingabruxia; all comb. nov. Pseudoluperus decipiens (Horn, 1893), originally described in Scelolyperus Crotch, 1874, is reduced to a junior synonym of Pseudoluperus longulus (LeConte, 1857), syn. nov. Trachyscelida dichroma Viswajyothi & Clark is proposed as a nom. nov. for Racenisa bicolor Bechyné, 1958 (not Agelastica bicolor LeConte, 1884), as both species are currently placed in the genus Trachyscelida Horn, 1893.